Children's Speech Recognition Under Mismatched Condition: A Review. Issue 2 (2nd July 2016) - Sunil, Y.; Prasanna, S.R. Mahadeva; Sinha, Rohit
ABSTRACT: Automatic speech recognition (ASR) is a task of converting speech to text. In this article, the ASR system trained using the speech of adult speakers and tested using the speech of child speakers is termed as children's speech recognition under mismatched condition. The mismatch refers to differences in the training and testing conditions due to the differences in the characteristics of speech signals belonging to adults and children. This mismatch results in significant degradation of the recognition performance. Therefore, there are several approaches in the literature to reduce the mismatch and hence improve the performance. The approaches may be broadly viewed of those trying to reduce the mismatch due to vocal tract length and excitation source characteristics. This article will review the works that have been done in this direction. A discussion on the literature critically comments on the existing works and suggests possible directions for future research.